Professional training: challenges and opportunities (Journal of Parents and Teachers, 2014)
In this article we are trying to dismantle myths and misconceptions about professional training, such as the myth that training is only for those who do not continue studying. Today, vocational training is a good option for further education, as three of our authors claim in the magazine.
Keywords: proffesional training; analysis; potencial; educational opportunity; students.